Chemical composition and apparent digestibility of green “orito” banana (Musa acuminata AA) meal in growing pigs - Caisedo, W.; Sánchez, J.; Viamontes, M.; Tapuy, A.; Estrada, C.; Flores, A.; Moya, C. (Cuban Journal of Agricultural Science, 2019)
The objective of this study was to determine the chemical composition and apparent digestibility of nutrients of meal of rejected “orito” banana (Musa acuminata AA) rejection meal. In samples of green banana meal were determined: dry matter (DM), organic matter (OM), crude protein (CP), crude fiber (CB), ash, ether extract (EE), nitrogen-free extract (NFE) and gross energy (GE). Three barrow male pigs with an average live weight of 38 ± 2 kg were used for the digestibility study of DM, OM, CP, CF, NFE and GE. The animals were distributed in three treatments: T0 (corn and protein concentrate), T20 and T40 (substitution of corn in 20 and 40 % for green banana meal in the diet) according to a 3 x 3 Latin square design. The data were processed by ANOVA and the mean comparison was made with the Duncan (P <0.05) test. The green “orito” banana meal, showed high content of DM (93.3 %), OM (90.28 %), NFE (91.33 %) and GE (16.98 kJ g DM-1). The best (P <0.05) uses of DM were obtained in T0 (87.07 %) and T20 (86.23 %) diets. The higher (P <0.05) use of OM (92.71 %) and CP (79.55 %) was obtained in the T20 diet. The highest (P <0.05) uses of CF and NFE were reached in the T20 (51.97 %, 74.14 %) and T40 (51.21 %, 73.37 %) diets. There were no differences (P>0.05) between treatments for the use of GE. The green “orito” banana meal showed high content of DM, OM, NFE, GE and did not affect the apparent digestibility coefficients of OM, CP, CF, NFE and GE when substituting the corn in the diet in 20 and 40 % which guarantees an energy food of appropriate nutritional characteristics for growing pigs. Key words: alternative food, energy source, green banana meal, pigs